A Brief Profile of the Status of Health and the Health System in South Africa : Background Note for the South Africa Systematic Country Diagnostic - Belli, Paolo (World Bank, Washington, DC, 2018)
South Africans suffer from a high burden of preventable illness and premature death, despite high expenditure on health. Over the last two decades some significant improvements have occurred in maternal and child health and in reducing the human immunodeficiency virus (HIV) burden. However, health indicators remain poor when compared to other countries at similar levels of development. Life expectancy is approximately 62 years, lower than average for lower middle-income countries. This study provides a brief profile of the status of health and the health system in South Africa, as a background note to the South Africa systematic country diagnostic.